A Comparative Analysis of the Economic Thought of Ibn Khaldun, Abu Hamid al-Ghazali, and Ibn Taymiyyah on Pricing and Market Mechanisms - Muhammad Rahmat; Siradjuddin Siradjuddin (Economics and Digital Business Review, 2026)
Markets play a crucial role in the economy. Islam recognizes the existence of market mechanisms, provided they operate perfectly. However, market distortions often occur due to seller manipulation. Therefore, this study aims to clarify the thinking of Ibn Khaldun, Al-Ghazali, and Ibn Taymiyyah on market mechanisms and the current market regulations. The methodology used in this paper is a qualitative literature study, examining the ideas and findings contained in articles, journals, books, and related theses to obtain scientific information. The results of this study indicate that Ibn Khaldun, Al-Ghazali, and Ibn Taymiyyah agree on pricing, stating that prices are determined by the forces of supply and demand. Only in cases where prices rise due to injustice and inequality in market mechanisms should the government intervene.